Igével, tollal és tettel. Pap Béla református lelkész életpályája (1907–1957) - BALOGH, Margit (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
By the Word, Pen, and Action. The Life and Career of Béla Pap, Pastor of the Reformed Church (1907–1957). The name of the martyred Reformed Church pastor Béla Pap has become syn-onymous with the newspaper Magyar Út (Hungarian Journey), which was a prominent forum of the national-populist writers’ movement that emerged as an unavoidable element of public life in Hungary in the 1930s. He published a number of articles that establish him as a socially sensitive intellectual thinker. He believed in creating a “national-populist” or “progressive” right wing and a modern Hungary. Anti-Semitism formed part of his ideology, but he did not foresee the consequences that eventually lead to the Holocaust. After the war, in the midst of the left’s growing dominance, he opposed the nationalization of schools and the agreement between the state and the church. He stood up for the Reformed Church’s farmer community whose members were branded as “kulaks” and for people who were displaced by the regime. His fate was sealed by his protest against the abolition of ecclesiastical autonomy. He was arrested on 27 November 1951 and sentenced to 4 years and 6 months of prison to be re-leased in the spring of 1956, but he could not return to his pastoral office. In the summer of 1957, he went on an excursion to the mountains – but was never seen again, dead or alive.